Understanding and Designing Head-to-Tail Cyclic Peptides - Slough, Diana P. (Biopolymers, 2018)
Cyclic peptides are an exciting class of molecules with a variety of applications. However, design strategies for cyclic peptide therapeutics, for example, are generally limited by a poor understanding of their sequence–structure relationships. This knowledge gap often leads to a trial-and-error approach for designing cyclic peptides for a specific purpose, which is both costly and time-consuming. Herein, we describe the current experimental and computational efforts in understanding and designing head-to-tail cyclic peptides along with their respective challenges. In addition, we provide several future directions in the field of computational cyclic peptide design to improve its accuracy, efficiency and applicability. These advances, combined with experimental techniques, shall ultimately provide a better understanding of these interesting molecules and a reliable working platform to rationally design cyclic peptides with desired characteristics.